Seismic loads : guide to the seismic load provisions of ASCE 7-16 - Charney, Finley Allan; Heausler, Thomas F.; Marshall, Justin D. (American Society of Civil Engineers, 2020)
Seismic Loads: Guide to the Seismic Load Provisions of ASCE 7-16 provides clear, authoritative explanations of the seismic design provisions contained in Minimum Design Loads and Associated Criteria for Buildings and Other Structures, ASCE/SEI 7-16. When used with the standard commentary, provided as a separate volume in ASCE 7-16, Seismic Loads assists structural engineers in applying the latest thinking in seismic design of new building structures. Authors Charney, Heausler, and Marshall present numerous detailed examples within the main 30 chapters of Seismic Loads. The examples help navigate structural engineers through the process of assessing conditions, including identifying occupancy, importance, and seismic design categories; determining the seismic requirements; and selecting a structural system. Topics include building irregularities, structural analysis, lateral system forces, load factors, drift, and P-delta effects. Major updates within the guide includeAn expanded introduction that provides a description of the history of the development of the ASCE 7 seismic provisions and how the provisions are updated on a 6-year cycle;Expanded examples of the use of Equivalent Lateral Force Analysis, Modal Response Spectrum Analysis, and Linear Response History Analysis, examples that utilize the same 8-story building;New examples covering Chapter 12 (complete seismic analysis of a simple building), Chapter 13 (nonstructural components), and Chapter 15 (nonbuilding structures); andAn expanded set of "Frequently Asked Questions," divided into topics of General Issues, Structural Design, and Structural Analysis.Seismic Loads is an essential companion to the standard ASCE/SEI 7-16 for all engineers, architects, and construction professionals who work on buildings in seismically active locations. About the AuthorsFinley A. Charney, Ph.D., P.E., is a professor of structural engineering at Virginia Tech and is president of Advanced Structural Concepts, Inc., both located in Blacksburg, Virginia.Thomas F. Heausler, P.E., S.E., is a structural engineering consultant in Leawood, Kansas.Justin D. Marshall, Ph.D., P.E., is a an associate professor of civil engineering at Auburn University in Auburn, Alabama.
Keywords: Earthquake resistant design -- Standards.; Earthquake resistant design -- Case studies.; elektronické knihy; electronic books